DETERMINATION OF FRESHNESS LEVEL FOR CHICKEN MEAT USING SMART LABEL BASED ON EXTRACT OF PURPLE SWEET POTATO ANTHOCYANIN - Andrew Setiawan Rusdianto; Andi Eko Wiyono; Nina Tauvika (BPFP Faperta UNIB, 2021)
Chicken meat is perishable food so it has a short shelf life. Nowadays, it has emerged Smart packaging equipped with smart label. Smart label based on extract anthocyanin purple sweet potato is solution to be used a determination the level of chicken meat freshness. The purpose of this study was to develop a smart label prototype based on anthocyanin extract and to determine its feasibility to determine the level of chicken meat freshness. Extract purple sweet potato anthocyanin was obtained by maceration method using methanol 96% solvent acidified with HCl 1%. The results of the anthocyanin extract had a pH of 5.58 ± 0.013 and value of anthocyanin 62.79 ± 0.558 mg / 100 g. The smart label shows the level of the chicken meat freshness with a change in color, where the purple color indicates the fresh chicken meat, the faded purple color indicates that the chicken is stay fresh, and the bluish purple smart label indicates the chicken is not fresh. The results of the feasibility of smart labels on pH stability experienced a color change in both acidic and alkaline situations, but were more stable in acidic conditions.